Maclurin Exhibits Antioxidant and Anti-Tyrosinase Activities, Suppressing Melanogenesis - Kyoung Mi Moon; Ju-Hye Yang; Min-Kyeong Lee; Eun-Bin Kwon; Jiwon Baek; Taehyeok Hwang; Jae-Il Kim; Bonggi Lee (MDPI AG, 2022)
Maclurin is rich in some edible fruits such as Morus alba (white mulberry) and Garcinia mangostana. Although maclurin showed anti-cancer and antioxidant effects, its roles in ultraviolet (UV)-induced melanogenesis have not been studied. Here, we investigated the effects of maclurin in melanogenesis using skin cells and a three-dimensional human skin model. When the cytotoxicity of maclurin was examined in B16F10 cells, no cytotoxicity was found up to 20 μM. Maclurin suppressed UVB-mediated tyrosinase activation and melanin accumulation in B16F10 cells without changes in mRNA levels of melanogenesis-related genes including tyrosinase, TRP1, TRP2, CREB, and MITF. Moreover, maclurin reduced melanin contents in melan-a cells, a cell line for normal melanocytes. When applied to a human skin model consisting of the epidermis and melanocytes, maclurin significantly reduced UVB-induced melanin accumulation (~47%) in a concentration-dependent manner based on microscopic observation and Fontana-Masson staining. Protein-ligand docking simulation followed by binding residue analysis showed that maclurin may bind to inactivate tyrosinase by forming multiple hydrogen bonds and hydrophobic and aromatic interactions with the residues of tyrosinase. Together, our study suggests that maclurin may be applied as an anti-melanogenic agent.